Pemilihan Model Ekonomi Empirik Dengan Pendekatan Koreksi Kesalahan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACTS For the last two decades, one of the major development in dynamic specifications has been an error correction model (ECM. The ECM can be motivated by optimizing behavior of economic agents in the presence of disequilibrium in the economy. In this case, the nets need to optimize subjet to a separate disequilibrium and adjustment costs. The disequilibrium cost is the cost associated with being out of long run equilibrium, whereas the adjustment cost is the cost associated with changes in the variables in question. This approach can not only capture the short- and long-run specifications and provide an attractive statistical framework, but is also consistent with the concept of cointegration or equilibrium relationships in economic rime series. It has also been widely used to model the dynamic specifications in economic analysis, because it has a number of advantages both in terms of its value in generating estimated regression equations with desirable statistical properties and in term of the ease with which such equations can be interpreted.